Sovereignty in European Context: how the European Union Reinforces National Sovereignty - Silva, Pedro Ferreira da (2011)
This paper aims to give a new perspective on the issue of sovereignty in the European context. In this context, we argue that the EU can contribute to increase Member States sovereignty. Many academic circles have advocated that the EU limits State’s sovereignty. This is why we intend to present a new approach to sovereignty in the European context. In order to present our argument we will discuss and debate the concept of sovereignty, both in the internal and external dimensions, which are associated with the concept of power. Then we will check if European states have the necessary means that enables them to project their power. We’ll also argue that there are real limitations, in current capabilities, and in resources availability needed to develop them in the future. We’ll also present the concept of politics of scale, arguing that we can apply this concept to develop state’s capabilities, which allow the necessary power projection, which enhances state’s sovereignty. This found that pooling and sharing will increase EU member states sovereignty, since it will allow a greater ability to project power, which is essential to support the external dimension of sovereignty. Thus, through a process of sharing and pooling member states will have the ability to defend their interests on a global scale, a level of intervention that will be denied if they choose to pursue individually. We also conclude that the current economic crisis may be used has a catalyst to deepen these mechanisms.